1989
DOI: 10.1007/bf00931066
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathogenicity ofNaegleria fowleri in mammalian cell cultures

Abstract: A total of 13 strains of Naegleria fowleri were cytopathogenic for lung, kidney, foreskin, ovary, connective tissue, neuroblastoma, laryngeal carcinoma, and cervical carcinoma mammalian cell lines. The strains of N. fowleri varied considerably in their ability to produce a cytopathic effect (CPE). Likewise, the different mammalian cell lines exhibited varying degrees of susceptability to the cytopathogenicity of the amebae. The African green-monkey kidney (Vero) cell line proved to be useful for assessing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…and Naegleria spp. (De Jonckheere 1980; John & John 1989). The pattern of CPE is different between amoeba species, but typically cytolysis is the end point and can occur in as little as 2 days following incubation (De Jonckheere 1980).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Naegleria spp. (De Jonckheere 1980; John & John 1989). The pattern of CPE is different between amoeba species, but typically cytolysis is the end point and can occur in as little as 2 days following incubation (De Jonckheere 1980).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to limited reproducibility and the influence of temperature, the in vitro cytopathogenicity of amoebae is also dependent upon the target cell used. For example, Naegleria fowleri is cytopathogenic for mammalian lung, kidney, foreskin, ovary, connective tissue, neuroblastoma and carcinoma cell lines, but the African green‐monkey kidney (Vero) cell line has proven to be the most effective in assessing the pathogenicity of strains of this species (John & John 1989). In the present study CPE of gill derived Neoparamoeba sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naegleria trophozoites can produce CPE by troglocytosis, contact-dependent lysis, or a combination of the two (8,10,15,16). Although trophozoites of Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 99%
“…1986). It is commonly accepted that the pathogenicity of N. fowleri can be increased by serial mouse brain passages (John & Howard, 1993;Marciano-Cabral, 1988) as well as by passages in tissue cultures (John & John, 1989). In vitro, it has been shown that trophozoites destroy their target cells by a combination of phagocytosis and the cytolytic action of secreted enzymes (Visvesvara & Callaway, 1974).…”
Section: Introductionmentioning
confidence: 99%